Pesticides and Soil Invertebrates: A Hazard Assessment - Gunstone, Tari; Cornelisse, Tara; Klein, Kendra; Dubey, Aditi; Donley, Nathan (Frontiers in Environmental Science, 2021)
Agricultural pesticide use and its associated environmental harms is widespread throughout the world. Efforts to mitigate this harm have largely focused on reducing pesticide contamination of the water and air, as runoff and pesticide drift are significant sources of offsite pesticide movement. Yet soil pesticide contamination can also result in environmental harm. Pesticides are often applied directly to soil as drenches and granules and increasingly in the form of seed coatings, making it important to understand how pesticides impact soil ecosystems. Soils contain an abundance of biologically diverse organisms that perform important functions such as nutrient cycling, soil structure maintenance, carbon transformation, and pest and disease regulation. Habitat loss and agrichemical pollution due to agricultural intensification have been identified as major driving factors in the decline of many terrestrial invertebrates. Here, we review nearly 400 studies on the effects of pesticides on non-target invertebrates that develop in the soil. This review encompasses 275 unique species, taxa or combined taxa of soil organisms and 284 different pesticide active ingredients or unique mixtures. We identified and extracted data on the following endpoints: mortality, abundance, biomass, behavior, reproduction, biochemical biomarkers, growth, richness and diversity, and structural changes. This resulted in an analysis of over 2,800 separate “tested parameters,” measured as a change in a specific endpoint following exposure of a specific organism to a pesticide. We found that 70.5% of tested parameters showed negative effects, whereas 1.4% and 28.1% of tested parameters showed positive or no significant effects from pesticide exposure, respectively. In addition, we discuss general effect trends among pesticide classes, taxa, and endpoints, as well as data gaps. Our review indicates that pesticides of all types pose a clear hazard to soil invertebrates. Negative effects are evident in both lab and field studies, across all studied pesticide classes, and in a wide variety of soil organisms and endpoints. This underscores the need for soil organisms to be represented in risk analyses of pesticides present in soil, and for any significant risk to be mitigated in a way that will reduce harm to soil organisms and the important ecosystem services they provide.